Natural products from the medicinal plant Duguetia staudtii (Annonaceae). (April 2019) - Ngouonpe, Alain W.; Mbobda, Alexis Sylvain W.; Happi, Gervais M.; Mbiantcha, Marius; Tatuedom, Ostend K.; Ali, Muhammad S.; Lateef, Mehreen; Tchouankeu, Jean Claude; Kouam, Siméon F.
Abstract: The phytochemical investigation of the ethyl acetate soluble fraction of Duguetia staudtii stem bark led to the isolation of eight compounds consisting into a new bisnorlignan named pachypolignan (1 ), a known bisnorlignan (2 ), four flavonoids (3 –6 ), one alkaloid (7 ), and one triterpenoid (8 ). The structures of all the compounds were established with help of spectral data including IR, UV, MS, 1D- and 2D-NMR spectroscopic data, as well as by comparison with previously-reported data in literature. The anti-inflammatory and urease inhibitory activities of the isolated compounds were assessed. Furthermore, the chemotaxonomic significance of these compounds was discussed. Highlights: One new pachypolignan was isolated from Dugetia staudtii. The structure was elucidated on the basis of spectroscopic data. The new compound, pachypolignan showed a urease inhibition activity.